The 1st International Electronic Conference on Food Science and Functional Foods 2020
DOI: 10.3390/foods_2020-07750
|View full text |Cite
|
Sign up to set email alerts
|

Avocado-Derived Biomass: Chemical Composition and Antioxidant Potential

Abstract: Avocado has become fashionable due to its great organoleptic and nutritional properties. It is consumed as a fresh product and it is also processed to obtain salad oil and guacamole. In all cases, the only usable portion is the pulp. Therefore, to be a more sustainable and profitable agribusiness, it is important to recognize which compounds from the peel and the stone waste can be converted into valuable bio-products. Therefore, their chemical composition was determined according to the National Renewable Ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Tis is in line with the study reported by Nguyen et al [40] where rice husk showed a higher biochar yield (35%) compared with bamboo biochar yield of 30%, which could be attributed to feedstock variation. Te higher biochar yield of ASB-450 °C than ASB-550 °C in this study is mainly attributed to the lower pyrolysis temperature and the higher lignin content [17,46] contained in its feedstock. Lignin content varies among diferent feedstock types, which afects the yield of the produced biochars pyrolyzed with similar temperatures [42,47,48].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Tis is in line with the study reported by Nguyen et al [40] where rice husk showed a higher biochar yield (35%) compared with bamboo biochar yield of 30%, which could be attributed to feedstock variation. Te higher biochar yield of ASB-450 °C than ASB-550 °C in this study is mainly attributed to the lower pyrolysis temperature and the higher lignin content [17,46] contained in its feedstock. Lignin content varies among diferent feedstock types, which afects the yield of the produced biochars pyrolyzed with similar temperatures [42,47,48].…”
Section: Discussionmentioning
confidence: 65%
“…Moreover, biochar from plant sources, particularly wood biochar has been widely characterized for application of agronomic purposes than biochar from animal sources and sewage sludge, because of the risk of contamination of heavy metals and other pollutants [9]. In addition, most biochar characterization studies have been carried out for agronomic purposes [10][11][12] including reclamation of degraded soils and enhance carbon sequestration to mitigate climate change [13], for the generation of bio-oil and energy [14], and for removing pollutants [15][16][17]. However, the characterization studies of avocado seed biochar have not been conducted to assess its impact on soil properties and crop production.…”
Section: Introductionmentioning
confidence: 99%
“…According to the study by García-Vargas et al (2020), the particle size of the sample was standardized at 500 µm and dried by air [14]. Finally, the powder was kept in a plastic bag until it could be analyzed further.…”
Section: Size Reduction and Sieve Analysismentioning
confidence: 99%
“…The resulting powder was sieved through a 40-gauge mesh and autoclaved at 121 °C (1.05 kg•cm −2 ) for 20 min. Subsequently, it was dried aseptically in a natural convection oven at a constant temperature of 70 °C for 72 h. The resulting avocado flour composed of approximately [acid-insoluble lignin 35.0%; polymeric sugars 23.6%; aqueous extractives 15.5%; and lipids and protein < 6% (García-Vargas et al 2020)] was used as the sole external substrate.…”
Section: Substrate Preparationmentioning
confidence: 99%